2018
DOI: 10.1084/jem.20172246
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 inhibitors as candidate therapeutics for cisplatin- and noise-induced hearing loss

Abstract: Using a high-throughput small molecule screen, Teitz et al. identify kenpaullone, a cyclin-dependent kinase 2 inhibitor, which when delivered locally confers protection against cisplatin- and noise-induced hearing loss in zebrafish, mice, and rats and reduces mitochondrial ROS production and cochlear cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(143 citation statements)
references
References 64 publications
12
108
0
4
Order By: Relevance
“…In this study, we showed that DOX treatment induced cardiomyocyte apoptosis through CDK2 activation. Our data are in agreement with most recent findings that activation of CDK2 by the DNAdamaging anticancer drug cisplatin results in cochlear cell apoptosis and hearing loss in rodents (29). Taken together, these findings suggested that CDK2 inhibition may have broad therapeutic applications against cancer treatmentrelated normal tissue toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we showed that DOX treatment induced cardiomyocyte apoptosis through CDK2 activation. Our data are in agreement with most recent findings that activation of CDK2 by the DNAdamaging anticancer drug cisplatin results in cochlear cell apoptosis and hearing loss in rodents (29). Taken together, these findings suggested that CDK2 inhibition may have broad therapeutic applications against cancer treatmentrelated normal tissue toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Kenpaullone promoted cell survival in the cochlea and prevented hearing loss by reducing cisplatin-induced mitochondrial production of ROS. 44…”
Section: Protective Agents-preclinical Studiesmentioning
confidence: 99%
“…These results highlight the utility of strategies that harness the results from genomic analyses to uncover additional agents to prevent ototoxicity, the validity of which should be tested in model organisms. Already established model organisms that have been successfully used to investigate potential otoprotectants include mouse cochlear explants, as well as zebrafish and murine models . Optimization of these model organisms is ongoing and of importance to studies who aim to move toward the implementation of otoprotectants in the clinical setting, a recent publication has described the development of a CIO mouse model that is consistent with the hearing loss phenotype observed in humans experiencing CIO …”
Section: Future Avenues Of Researchmentioning
confidence: 99%
“…Already established model organisms that have been successfully used to investigate potential otoprotectants include mouse cochlear explants, as well as zebrafish and murine models. 63 Optimization of these model organisms is ongoing and of importance to studies who aim to move toward the implementation of otoprotectants in the clinical setting, a recent publication has described the development of a CIO mouse model that is consistent with the hearing loss phenotype observed in humans experiencing CIO. 64 Expanding research beyond a single trait A final avenue of interest would be to examine the relevance of genetic factors that are associated with CIO to other traits.…”
Section: Future Avenues Of Research Standardization Of Phenotypes Andmentioning
confidence: 99%